Histological Patterns of Epithelial Alterations in Keratoconus. (30th July 2020) - Crespo Millas, Sara; López, José Carlos; García-Lagarto, Elena; Obregón, Estibaliz; Hileeto, Denise; Maldonado, Miguel J.; Pastor, J. Carlos
Abstract : Purpose . The purpose of this study was to confirm the presence of specific patterns of epithelial response in corneal buttons from keratoconus patients. Methods . This was a retrospective and descriptive study. 90 penetrating keratoplasty specimens obtained from patients diagnosed with keratoconus were evaluated using bright-field microscopy. Morphologically identifiable characteristics including epithelial cell density and epithelial thickness were analyzed on hematoxylin and eosin- (H&E-) and periodic acid of Schiff- (PAS-) stained slides. Results . Three distinctive patterns of epithelial alteration of the central cornea were established. Pattern 3, in which the central epithelium was as thick as peripheral epithelium, was the commonest (44.4%), followed by the pattern 2, defined as central epithelium thinner than periphery epithelium (38.9%), and the uncommonest pattern was number 1, with central epithelium thicker than the periphery (16.7%). Conclusions . Three distinctive histologic patterns that could potentially have a diagnostic and prognostic value in keratoconus patients were found.